Prelude to decolonisation in West Africa - Nordman, C (1976)
﻿ This study sets out to examine the development of British colonial policy towards West Africa between the years 1938 and 1947. It is primarily a study of the so-called 'official mind' of British colonialism because, as the sources indicate, the nationalists were mainly excluded from the review process. It has been decided to begin the thesis with the Colonial Secretaryship of Malcolm MacDonald. With the assistance of the West Indian Crisis, which propelled the colonial issue into the political arena in Britain, and Hailey's African Survey, which set out the deficiencies of British rule in Africa, MacDonald was supplied with the political lever and the requisite guidelines for him to successfully initiate a review of colonial policy in 1938. In particular MacDonald wished to see resolved the potential contradictions which existed in Britain's colonial policy. As he put it, "Important decisions may have to be taken in order to prevent Native Authorities on the one hand and Legislative Councils on the other from developing along divergent lines with undesirable results". This theme dominated the British West African policy review until 1947, by which time constitutions designed to effect such a harmony had either been implemented or announced. [Please see pdf. for full abstract.]